My name is Lucy Barton [large type] : a novel - Strout, Elizabeth (Center Point Large Print, 2016)
"Lucy Barton is recovering slowly from what should have been a simple operation. Her mother, to whom she hasn't spoken for many years, comes to see her and a simple hospital visit becomes a portal to the most tender relationship of all--the one between mother and daughter"--